Structure of salt solution in polar dielectric liquids and electrically-induced separation of solvated ions; Физико-технические проблемы в науке, промышленности и медицине - Shamanin I. V. Igor Vladimirovich; Kazaryan M. A.; Gofman V. N. Valery Nikolaevich; Timchenko S. N. Sergey Nikolaevich; Tuksov I. V. (Физико-химические и изотопные технологии в науке, промышленности и медицине, 2016)
Заглавие с экрана